Rapid prototyping and inclined plane technique in the treatment of maxillofacial malformations in a fox - Freitas, Elisangela P.; Rahal, Sheila C.; Teixeira, Carlos R.; Silva, Jorge V. L.; Noritomi, Pedro Y.; Villela, Carlos H. S.; Yamashita, Seizo [UNESP] (My University, 2010)
An approximately 9-month-old fox (Pseudabpex vetulus) was presented with malocclusion and deviation of the lower jaw to the right side. Orthodontic treatment was performed using die inclined plane technique. Virtual 3D models and prototypes of the head were based on computed tomography (CT) image data to assist in diagnosis and treatment.